Eksistensi Pos Bantuan Hukum (Posbakum) di Pengadilan Tata Usaha Negara Denpasar - Ni Nyoman Gabriella Christiawan Putri; Anak Agung Sagung Laksmi Dewi; I Nyoman Sutama (Warmadewa Press, 2021)
Due to the development of law, legal assistance activities especially for the people that were not able to lay in law as well as the more widely in the community, which is now already so developed in Indonesia. As for the laws that regulate clearly about legal aid is law number 16 of the year 2011. Therefore, the formulation of the problem of this thesis are: 1) how the post position of legal aid (Posbakum) in providing service in PTUN Denpasar, 2) is the function of granting legal aid service in Denpasar PTUN. Research methods used to answer the problems is the normative method, a method that uses a variety of legal research legal materials of primary and secondary legal materials such as legislation, legal theory, and can be either the opinions of scholars. Based on the above research, it is very helpful to every person to obtain legal aid in legal proceedings to obtain justice. In this study the authors raised the existence of legal aid Post title (Posbakum) in the courts of the country of Denpasar.